2010
DOI: 10.1037/a0019501
|View full text |Cite
|
Sign up to set email alerts
|

Leadership perceptions as a function of race–occupation fit: The case of Asian Americans.

Abstract: On the basis of the connectionist model of leadership, we examined perceptions of leadership as a function of the contextual factors of race (Asian American, Caucasian American) and occupation (engineering, sales) in 3 experiments (1 student sample and 2 industry samples). Race and occupation exhibited differential effects for within- and between-race comparisons. With regard to within-race comparisons, leadership perceptions of Asian Americans were higher when race-occupation was a good fit (engineer position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
251
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(269 citation statements)
references
References 101 publications
(195 reference statements)
10
251
0
Order By: Relevance
“…In this way, leadership prototypes are dynamically derived and can be adjusted to many contextual features upon use (e.g., organizational culture, task characteristics, and characteristics of the perceiver) as sensory input causes different sets of nodes to become active (Foti, Knee, & Backert, 2008;Hanges, Lord, & Dickson, 2000;Lord et al, 2001). The result is that across different situations, certain individuals may be more (or less) likely to emerge as leaders based on how contextual features constrain which parts of the connectionist network becomes active or suppressed (Lord et al, 2001; see also Sy et al, 2010). In a competitive environment, for instance, leadership prototypes may center more on individual characteristics that emphasize 'dominance' and 'aggression.'…”
Section: Moderators and Their Effects On Leadership Perceptionmentioning
confidence: 98%
“…In this way, leadership prototypes are dynamically derived and can be adjusted to many contextual features upon use (e.g., organizational culture, task characteristics, and characteristics of the perceiver) as sensory input causes different sets of nodes to become active (Foti, Knee, & Backert, 2008;Hanges, Lord, & Dickson, 2000;Lord et al, 2001). The result is that across different situations, certain individuals may be more (or less) likely to emerge as leaders based on how contextual features constrain which parts of the connectionist network becomes active or suppressed (Lord et al, 2001; see also Sy et al, 2010). In a competitive environment, for instance, leadership prototypes may center more on individual characteristics that emphasize 'dominance' and 'aggression.'…”
Section: Moderators and Their Effects On Leadership Perceptionmentioning
confidence: 98%
“…Moreover, social perceivers give non-whites less credit for their success and hold lower expectations for their future success (Rosette, Leonardelli, & Phillips, 2008). Similarly, Asian Americans are significantly less likely to be viewed as leaders than Caucasian Americans (Sy et al, 2010). Thus a mismatch between racial stereotypes and the job role (e.g., leader) may promote a bias against non-white leaders, whereby they are given consistently lower ratings.…”
mentioning
confidence: 98%
“…Given the historic and current overrepresentation of Whites in leadership positions in the USA (Bell et al 2014;Maume 2012;Stainback and Tomaskovic-Devey 2009), it is not surprising that research has found that being White is a prototypical characteristic of a leader (e.g., Carton and Rosette 2011;Rosette et al 2008;Sy et al 2010). During the leader categorization process, non-White targets have a higher probability of receiving a non-leader designation, leading to a less favorable evaluation of effectiveness than White targets.…”
Section: Leadership Categorization Theory and Racementioning
confidence: 93%